Microbial community composition of terrestrial habitats in East Antarctica with a focus on microphototrophs - Pushkareva, Ekaterina; Elster, Josef; Kudoh, Sakae; Imura, Satoshi; Becker, Burkhard (Frontiers in Microbiology, 2024)
The Antarctic terrestrial environment harbours a diverse community of microorganisms, which have adapted to the extreme conditions. The aim of this study was to describe the composition of microbial communities in a diverse range of terrestrial environments (various biocrusts and soils, sands from ephemeral wetlands, biofilms, endolithic and hypolithic communities) in East Antarctica using both molecular and morphological approaches. Amplicon sequencing of the 16S rRNA gene revealed the dominance of Chloroflexi, Cyanobacteria and Firmicutes, while sequencing of the 18S rRNA gene showed the prevalence of Alveolata, Chloroplastida, Metazoa and Rhizaria. This study also provided a comprehensive assessment of the microphototrophic community revealing a diversity of cyanobacteria and eukaryotic microalgae in various Antarctic terrestrial samples. Filamentous cyanobacteria belonging to the orders Oscillatoriales and Pseudanabaenales dominated prokaryotic community, while members of Trebouxiophyceae were the most abundant representatives of eukaryotes. In addition, the co-occurrence analysis showed a prevalence of positive correlations with bacterial taxa frequently co-occurring together.